What Did the Maoists Ever Do for Us? Education and Marriage of Women Exposed to Civil Conflict in Nepal - Valente, Christine (2012)
Between 1996 and 2006, Nepal experienced violent civil conflict as a consequence of a Maoist insurgency, which many argue also brought about an increase in female empowerment. This paper exploits within and between-district variation in the intensity of violence to estimate the impact of conflict intensity on two key areas of the life of women in Nepal, namely education and marriage. Overall conflict intensity had a small, positive effect on female educational attainment, whereas abductions by Maoists had the reverse effect. Male schooling was not significantly affected by either conflict measure. Conflict intensity and Maoist abductions during school age both increased the probability of early female marriage, but exposure to conflict during marriageable age does not appear to have affected women's long-term marriage probability.